A Cellular Automata Based Verifiable Multi‐secret Sharing Scheme Without a Trusted Dealer. Issue 2 (1st March 2017) - Li, Meng; Yu, Jia; Hao, Rong
Abstract : We proposed a verifiable multi‐secret sharing scheme without a dealer. We use cellular automata, having the properties of linear computations and parallel computations, to construct our scheme. The linear computational property makes it possible to build a scheme without the assistance of a trusted dealer, and the parallel computational property contributes to the high efficiency of the scheme. Hash function is used to realize the verification of shares, which also makes our scheme more efficient. The security of the scheme is also analyzed.